Here's the question you clicked on:
stephcanie
Solve the system using elimination. 2x+3y=6 5x-y=-19
To eliminate one of the variables, make one of equations have equal variables just negative and positive. To do this, multiply the second equation by 3 to get -y to -3y, but you must multiply the whole equation. 15x-3y=-57 2x+3y=6
Add the equations together now! 15x+2x=17x -57+6=-51 17x=-51 x=-3
Whoops, made a mistake.
First equal one of the variable in both of the equations |dw:1352832467734:dw|
|dw:1352832598245:dw|
@ajprincess m i right becoz i m nt ure about this
Thanks guys this really helped.
When u multiply the second equation by 2 u get 10x-2y=-38. Let us name that as equation (3). The resultant equation u get by multiplying the first equation by 5 is 10x+15y=30. Let us name this equation(4). Subtracting (3) from (4) (4)-(30=> 10x+15y-10x+2y=30-(-38) 17y=68 y=68/17 y=4
@jiteshmeghwal9 guess u forgot abt the negative sign in front of 38.
oops... yeah sorry
that's k.:) that happens sometimes to me too.:)
U really are a very intelligent OS user :)
Thanx for the compliment.:)
@stephcanie do u get t?
No need of thanx.... u really deserve it :)